2010
DOI: 10.1016/j.psychres.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of recovery of social functioning in types I and II bipolar disorder patients

Abstract: Since bipolar disorder (BPD) patients are often functionally impaired, and factors associated with recovery from disability are largely unknown, we investigated demographic, clinical, and neurocognitive correlates of current social functional recovery in 65 stable participants diagnosed with DSM-IV type I (n=42) or II (n=23) BPD. Regaining highest previous levels of social functioning was rated with the Interpersonal Relationships Questionnaire. We also considered neuropsychological test findings as well as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…Using the SDS, we showed recovery in 50% of patients at 6 months and 100% at 1 year, which was maintained at 2 years. Many of the studies conducted in the past 5 years have not demonstrated such a high degree of functional recovery, with rates of approximately 35% to 65% by years (Conus et al, 2006;Dickerson et al, 2010;Kauer-Sant'Anna et al, 2009;Wingo et al, 2010). Our patients were more severely affected than BPD patients previously reported in the literature (Gutierrez-Rojas et al, 2011) but made better long-term functional recovery, making the effect all the more impressive.…”
Section: Discussionsupporting
confidence: 40%
“…Using the SDS, we showed recovery in 50% of patients at 6 months and 100% at 1 year, which was maintained at 2 years. Many of the studies conducted in the past 5 years have not demonstrated such a high degree of functional recovery, with rates of approximately 35% to 65% by years (Conus et al, 2006;Dickerson et al, 2010;Kauer-Sant'Anna et al, 2009;Wingo et al, 2010). Our patients were more severely affected than BPD patients previously reported in the literature (Gutierrez-Rojas et al, 2011) but made better long-term functional recovery, making the effect all the more impressive.…”
Section: Discussionsupporting
confidence: 40%
“…We expected that a more severe course of illness would indicate poorer interpersonal relationship functioning, as has been found in previous research (Johnson et al, 2003, Sullivan and Miklowitz, 2010, Uebelacker et al, 2006, Wingo et al, 2010). Next, we examined whether changes in mood episode severity (depression and mania) predicted changes in interpersonal functioning, or vice versa, over time (comparisons of the same participant at different time points, or within-person analyses).…”
Section: Introductionmentioning
confidence: 78%
“…In studies of BP adolescents and adults, interpersonal difficulties have been associated with greater symptom severity and higher rates of relapse, when measured at the same time point (i.e., cross-sectionally) (Johnson et al, 2003, Sullivan and Miklowitz, 2010, Uebelacker et al, 2006, Wingo et al, 2010). Cross-sectional studies, however, do not elucidate the associations between mood and interpersonal functioning over time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their positive psychotic symptoms, this group of patients also experienced various mood problems. Patients with mood disturbances tend to be impaired in their social interactions (Schoeyen et al 2011; Wingo et al 2010). Since affective and non- affective face information plays a major role in social interactions (Haxby et al 2002), it would be expected that face perception and mood disturbances would be associated with each other as well, and thus that patients with schizoaffective disorder would be more deficient in face perception than schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%